2021
DOI: 10.3390/app11198807
|View full text |Cite
|
Sign up to set email alerts
|

Indoor and Outdoor Performance of an Enhanced Photovoltaic Panel through Graphene/Fins/Phase Change Materials

Abstract: The operative temperature of a photovoltaic cell influences the electric conversion yield. This can be enhanced by cooling the panel. Among the studied solutions, phase change materials (PCM) exploit latent heat and absorb a large amount of energy at a nearly constant temperature. PCMs suffer from a low thermal conductivity. Under these premises the paper presents a hybrid graphene/fins/PCM cooling system to maximize efficiency gains and thermal recovery. An indoor laboratory characterization, under a solar si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The present research is influenced by Hasan et al 26 which is similar to Colarossi and Principi 19 for PV‐PCM systems. In Hasan's study, two PV‐PCM systems were developed using Capric‐palmitic acid and calcium chloride hexahydrate as PCMs and performance comparison with reference PV was conducted.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…The present research is influenced by Hasan et al 26 which is similar to Colarossi and Principi 19 for PV‐PCM systems. In Hasan's study, two PV‐PCM systems were developed using Capric‐palmitic acid and calcium chloride hexahydrate as PCMs and performance comparison with reference PV was conducted.…”
Section: Introductionmentioning
confidence: 67%
“…In this comparative study, the PV/T‐PCM system showed the higher heat storage potential among other systems. To compare the performance of fins equipped PV‐PCM system with a simple PV panel Colarossi and Principi 19 used graphene in PCM behind PV panel. The comparison was done under indoor and outdoor conditions with a simple PV panel for surface temperature and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…By implementing efficient PV systems, the safety of the users of the electricity supply is increased [4,5]. These systems also reduce the vulnerability of European space and could eliminate future energy crises or the lack of an energy supply.…”
Section: Introductionmentioning
confidence: 99%